What determines adult cognitive skills?: Impacts of preschooling, schooling, and post-schooling experiences in Guatemala - Behrman, Jere R.; Hoddinott, John F.; Maluccio, John; Soler-Hampejsek, Erica; Behrman, Emily L.; Martorell, Reynaldo; Ramirez-Zea, Manuel; Stein, Aryeh D. (International Food Policy Research Institute, 2008)
Most investigations into the importance and determinants of adult cognitive skills assume that (1) they are produced primarily by schooling, and (2) schooling is statistically predetermined or exogenous. This study uses longitudinal data collected in Guatemala over 35 years to investigate production functions for adult cognitive skills—that is, reading-comprehension skills and nonverbal cognitive skills—as being dependent on behaviorally determined preschooling, schooling, and post-schooling experiences. We use an indicator of whether the child was stunted (child height-for-age Z-score < –2) as our representation of preschooling experiences, and we use tenure in skilled occupations as our representation of post-schooling experiences. The results indicate that assumptions (1) and (2) lead to a substantial overemphasis on schooling and an underemphasis on pre- and post-schooling experiences. The magnitudes of the effects of these pre- and post-schooling experiences are large. For example, the impact on reading-comprehension scores of not being stunted at age 6 is equivalent to the impact of four grades of schooling. These findings also have other important implications. For example, they (1) reinforce the importance of early life investments; (2) point to limitations in using adult schooling to represent human capital in the cross-country growth literature; (3) support the importance of childhood nutrition and work complexity in explaining the “Flynn effect,” or the substantial increases in measured cognitive skills over time; and (4) lead to doubts about the interpretations of studies that report productivity impacts of cognitive skills without controlling for skill endogeneity.